2017
DOI: 10.2147/ijn.s130094
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid-functionalized drug delivery platform of resveratrol based on Pluronic 127/D-α-tocopheryl polyethylene glycol 1000 succinate mixed micelles

Abstract: A folic acid (FA)-functionalized drug vehicle platform based on Pluronic 127 (P127)/D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) mixed micelles was orchestrated for an effective delivery of the model drug resveratrol in order to address the problem of poor water solubility and rapid metabolism of resveratrol and improve its targeted accumulation at tumor site. The FA-decorated mixed micelles were prepared using thin-film hydration method and optimized by central composite design approach. The micel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 39 publications
1
35
1
Order By: Relevance
“…This result is in agreement with the previously reported higher uptake of covalent-conjugated FA-HSA NPs into cancer cells [51]. Recently, Hao et al reported the superior cytotoxicity of folate-targeted RSV-loaded Pluronic/TPGS- mixed MCs (IC 50 = 27.89 μg/ml) against folate receptor-overexpressing MCF-7 cells compared with free RSV (137.58 μg/ml) after 48 h [52]. Furthermore, the structure resemblance of phospholipid bilayer to the lipid content of the mammalian cellular membrane can increase membrane penetration.…”
Section: In Vitro Hemolysis Testsupporting
confidence: 92%
“…This result is in agreement with the previously reported higher uptake of covalent-conjugated FA-HSA NPs into cancer cells [51]. Recently, Hao et al reported the superior cytotoxicity of folate-targeted RSV-loaded Pluronic/TPGS- mixed MCs (IC 50 = 27.89 μg/ml) against folate receptor-overexpressing MCF-7 cells compared with free RSV (137.58 μg/ml) after 48 h [52]. Furthermore, the structure resemblance of phospholipid bilayer to the lipid content of the mammalian cellular membrane can increase membrane penetration.…”
Section: In Vitro Hemolysis Testsupporting
confidence: 92%
“…This phenomenon could be due to the ligands-mediated targeting of TPP-TPGS-modified LPNs. 45 In vivo infarct therapy effect was evaluated by measuring the infarct size. Infarct size is conceived as one of the critical indices for evaluating the cardiac damage in the generation of ischemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Encapsulation of polyphenols enhances the bioavailability of these micronutrients in solution [1][2][3][4][5]34]. Folic acid functionalized drug delivery system based on resveratrol is known [35]. Resveratrol-folic acid-chitosan-100 5.9 (±0.9) 1.5 65…”
Section: Discussionmentioning
confidence: 99%